Understanding organization-customer links in a service setting in Russia. (May 2022) - Ashill, Nick; Abuelsamen, Amjad; Gibbs, Tanya; Semaan, Rania W.
Abstract: This study examines the effect of management commitment to service quality on customer satisfaction through the mediating links of service climate and core and relational service performance in a high-power distance culture. Data were collected using a survey distributed to the FLEs and customers of branches of a Russian retail bank. Study findings demonstrate that branch service climate mediates the management commitment to service quality – service performance relationship and that this indirect effect is stronger on core service performance relative to relational service performance. Contrary to expectations, our findings demonstrate the importance of relational service performance relative to core service performance as a mediator of the branch service climate – branch customer satisfaction relationship. Implications of these novel findings and future research directions are discussed.